The Effect of Service Quality, Work Ethic and Discipline on Community Satisfaction at the Muara Enim Sub-District Office, Muara Enim Regency - A. Rakhim; Sulbahri Madjir; Nisma Aprini (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2024)
The author conducted research with the aim of knowing and analyzing the effect of service quality, work ethic and discipline individually and collectively on community satisfaction at the Muara Enim District Office, Muara Enim Regency. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test, normality test. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial test simultaneous test and the coefficient of determination. The results showed that service quality has a significant effect on community satisfaction at the Muara Enim District Office, Muara Enim Regency. Work ethic has a significant effect on community satisfaction at the Muara Enim District Office, Muara Enim Regency. Discipline has a significant effect on community satisfaction at the Muara Enim District Office, Muara Enim Regency. Quality of service, work ethic and discipline have a significant effect on community satisfaction at the Muara Enim District Office, Muara Enim Regency.